Term ve preterm bebek annelerinin bebeklerini algılama durumları - (:unkn) unknown (My University, 2010)
Amaç. Term ve preterm bebek annelerinin bebeklerini nasıl algıladıklarını ve bu algıyı etkileyen faktörleri belirlemektir. Yöntem. Araştırmanın örneklemini 67 term, 41 preterm primipar bebek annesi oluşturmuştur. Tanıtıcı anket formu ve Yenidoğanı Algılama Ölçeği kullanılarak elde edilen veriler yüzdelik, Ki-kare ve iki ortalama arasındaki farkın önemlilik testileri ile değerlendirilmiştir. Bulgular. Preterm bebek annelerinin bebeklerini daha negatif algıladıkları, doğum öncesi bilgi almamanın negatif algılamaları ve bebeğin istendik cinsiyette doğmasının pozitif algılamaları artırdığı bulunmuştur. Her iki grup arasındaki eğitim durumu, bebek bakımı konusunda yardımcının olması, doğum öncesi bilgi alma durumu ve annelerin bebeklerini kucaklarına alma zamanları yönünden istatistiksel fark anlamlıdır. Sonuç. Bebeklerin preterm doğması anneleri tarafından negatif algılanmalarını etkilemektedir.

Aim. The aim of this study was to define how term and preterm baby mothers perceive their babies and the factors affecting this perception. Method. The sampling of research included 67 term and 41 preterm primiparous mothers. The data derived by using introductory survey form and Neonatal Perception Scale has been evaluated through percentage, Chi-square and t tests. Results. It has been found that preterm baby mothers perceived their babies more negative, that not receiving information before delivery raised negative perception and that the baby who was born with desirable gender raised positive perception. Between either of the two groups, the statistical difference is significant with regards to education, having a helpmate for baby care, the state of receiving information before delivery and the time of mothers’ embracing their babies. Those babies’ preterm birth affects their positive perception by their mothers. Conclusion. The negative perception of mothers were influenced by the preterm birth of their babies.
Perception of term and preterm babies by their mothers
Keywords: Hemşirelik; Kadın Araştırmaları